Adjuvant efficacy of G2 (buffalo spleen extraction) against Yersinia septicemia in rainbow trout (Onchorhynchus mykiss). Issue 82 (November 2018) - Shafie, Shafigh; Soltani, Elahe; Soltani, Mehdi; Hazrati, Saleh Mohaghegh
Abstract: Adjuvant effect of G2 (extraction of buffalo spleen) was assessed in intraperitoneally immunized rainbow trout (100–150 g) with killed- Y. ruckeri bacterin biotype I [0.1 mL (1 × 10 7  cells/fish) of vaccine diluted with the adjuvant in a ratio of 1:1 (V/V)] at 12.4 ± 1.3 °C for 10 weeks. Leukocyte and lymphocyte counts, anti- Y. ruckeri antibody titer and relative percent survival (RPS) in fish vaccinated with vaccine containing the adjuvant were significantly higher than the immunized fish with Y. ruckeri antigen alone throughout the experiment (P < 0.05), but neutrophils count and lysozyme activity were mostly significantly higher in the latter group (P < 0.05). No difference was seen in the complement activity between vaccinated fish containing the adjuvant and vaccine alone (P > 0.05). The results of this work for the first time demonstrated that inclusion of G2 as an adjuvant in Y. urckeri vaccine can improve the efficacy of the vaccine against Yersinia septicemia in rainbow trout. Highlights: G2 adjuvant enhanced efficacy and potency of Y. ruckeri vaccine in fish. G2 adjuvant increased survival of vaccinated trout against Yersinia septicemia. G2 adjuvant increased specific antibody level in vaccinated fish with Yersinia vaccine. G2 adjuvant enhanced total leukocyte and lymphocyte counts in vaccinated fish.